2005
DOI: 10.1186/1897-4287-3-2-59
|View full text |Cite
|
Sign up to set email alerts
|

The 3020insC Allele of NOD2 Predisposes to Cancers of Multiple Organs

Abstract: The NOD2 gene has been associated with susceptibility to Crohn's disease and individuals with Crohn's disease are at increased risk for cancer at a number of organ sites. We studied the association between the 3020insC allele of the NOD2 gene and cancer among 2604 cancer patients and 1910 controls from Poland. Patients were diagnosed with one of twelve types of cancer in the Szczecin region between 1994 and 2004. Significant associations were found for colon cancer (OR = 1.8; 95% CI 1.2 to 2.6), for lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 25 publications
1
40
2
Order By: Relevance
“…In several recent studies, it has been shown that at least one relatively common mutation in an inflammatory response regulator NOD2/ CARD15 is associated with an increased risk of malignancy of the bowel and the breast [5][6][7]. The same mutation has been reported to be one of the possible lung cancer genes [8]. The NOD2/CARD15 gene was initially identified as a Crohn's disease risk factor since biallelic mutations of the gene were shown to confer a $30-fold risk of Crohn's disease and a $3-fold risk if heterozygous compared to individuals not harboring changes in this gene [9,10].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In several recent studies, it has been shown that at least one relatively common mutation in an inflammatory response regulator NOD2/ CARD15 is associated with an increased risk of malignancy of the bowel and the breast [5][6][7]. The same mutation has been reported to be one of the possible lung cancer genes [8]. The NOD2/CARD15 gene was initially identified as a Crohn's disease risk factor since biallelic mutations of the gene were shown to confer a $30-fold risk of Crohn's disease and a $3-fold risk if heterozygous compared to individuals not harboring changes in this gene [9,10].…”
Section: Introductionmentioning
confidence: 97%
“…Since common mutations in the NOD2/CARD15 gene have already been associated with an increased odds ratio of developing cancers of the bowel or breast, and with the increased incidence of malignancy in Crohn's disease and an overall increase in malignancies at other sites including breast, lung, larynx and ovary [8], we reasoned that there may be common genetic factors associated with breast cancer patients who reported cases of lung cancer within their families. To investigate the possibility that NOD2/CARD15 may be associated with at least a proportion of breast and lung cancer families, an investigation into 4107 consecutively collected breast cancer patients and 389 consecutively collected lung cancer patients was undertaken and the results compared to 2068 control samples.…”
Section: Introductionmentioning
confidence: 98%
“…A second genetic factor that has been linked to breast cancer risk is NOD2 [8] which has also been associated with an increased risk of lung cancer and a suggestion that it is also associated with laryngeal cancer risk [9]. In particular, the NOD2 3020insC polymorphism seems to be associated with an approximate 2-fold increased susceptibility to early-onset breast cancer and laryngeal cancer [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…In particular, the NOD2 3020insC polymorphism seems to be associated with an approximate 2-fold increased susceptibility to early-onset breast cancer and laryngeal cancer [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…Statistic v 2 = 9.220; p = 0.010 Lubiński et al reported that NOD2 gene is associated with an increased risk of colon cancer and the presence of the NOD2 3020insC allele increases the lifetime risk of cancer by approximately 25-35 %. They also found that presence of the NOD2 3020insC allele increase the risk of lung cancer by 1.7 times compared to control [26].…”
Section: Discussionmentioning
confidence: 93%